2017
DOI: 10.1017/s0022215117000998
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes following salvage surgery for oropharyngeal squamous cell carcinoma: systematic review

Abstract: Improvements in treatment modalities for recurrent oropharyngeal squamous cell carcinoma were associated with improvements in two-year overall survival rates, with minimal change to five-year overall survival rates. Various factors were identified as being associated with long-term overall survival, thus assisting clinicians in patient counselling and selection for salvage surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…Thus, the miRNA content of circulating small extracellular vesicles has the potential to provide a unique molecular signature for multiple possibilities such as diagnosis, prognosis and surveillance of cancers [ 10 ]. In the event of recurrence, a systematic review found that success of salvage surgery in OPSCC recurrence is dependent on early recognition of such disease [ 11 ]. A biomarker that identifies the presence of residual or recurrent cancers prior to clinical evidence of such disease would facilitate early salvage options.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the miRNA content of circulating small extracellular vesicles has the potential to provide a unique molecular signature for multiple possibilities such as diagnosis, prognosis and surveillance of cancers [ 10 ]. In the event of recurrence, a systematic review found that success of salvage surgery in OPSCC recurrence is dependent on early recognition of such disease [ 11 ]. A biomarker that identifies the presence of residual or recurrent cancers prior to clinical evidence of such disease would facilitate early salvage options.…”
Section: Introductionmentioning
confidence: 99%
“…These patients were almost exclusively treated with open surgery. A recent review of 18 articles showed similar results (45). Favorable results have also been reported using TORS for salvage surgery in a selected group of patients with early-stage recurrence.…”
Section: Surgerymentioning
confidence: 71%
“…This consideration is especially important for patients with HPV-associated disease, a population with a favorable prognosis. Post-CRT neck dissection has important implications on long-term quality of life as it is associated with a higher rate of post-operative complications (17). Therefore, a literature review was performed with the PubMed Database to investigate potential strategies for improvement of post-CRT treatment assessment of the neck in patients with HPV-associated OPSCC.…”
Section: Introductionmentioning
confidence: 99%